New species, new combination and new records of the genus Mallada navas (Neuroptera Chrysopidae) from Western Himalaya, India - Bhattacharya, D.K.; Dey, S.R. (2002)
Mallada ectoflagellata, a new species is described from Western Himalaya, India. New combination is established in the case of Chrysopidia garhwalensis Ghosh transferred to Genus Mallada. Three species viz. Mallada obvia Hölzel, Mallada astur (Banks) and Mallada alcestes (Banks) are new records from Western Himalaya, India.
Includes bibliographical references (page 47)
Keywords: Entomology; Mallada navas (Neuroptera: Chrysopidae) -- Description of new species -- Western Himalaya (India)